2008
DOI: 10.1111/j.1469-1809.2008.00447.x
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Gender‐Specific Genetic Factors to Osteoporosis Risk

Abstract: SummaryCommon diseases result from the complex relationship between genetic and environmental factors. The aim of this review is to provide perspective for a conceptual framework aimed at studying the interplay of gender-specific genetic and environmental factors in the etiology of complex disease, using osteoporosis as an example.In recent years, gender differences in the heritability of the osteoporosis-related phenotypes have been reported and sex-specific quantitative-trait loci were discovered by linkage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 142 publications
1
51
0
3
Order By: Relevance
“…We previously reported that PAI-1 is involved in the pathogenesis of type 1 diabetic osteoporosis in female mice but not in male mice (16). Studies have suggested that a protein linked to the sex chromosomes is associated with the sex differences in the prevalence of metabolic abnormality and osteoporosis (49,50). This suggests that a protein linked to a sex chromosome might be responsible for the sex differences observed in the current study.…”
Section: Diabetesdiabetesjournalsorg Tamura and Associatesmentioning
confidence: 42%
“…We previously reported that PAI-1 is involved in the pathogenesis of type 1 diabetic osteoporosis in female mice but not in male mice (16). Studies have suggested that a protein linked to the sex chromosomes is associated with the sex differences in the prevalence of metabolic abnormality and osteoporosis (49,50). This suggests that a protein linked to a sex chromosome might be responsible for the sex differences observed in the current study.…”
Section: Diabetesdiabetesjournalsorg Tamura and Associatesmentioning
confidence: 42%
“…We did not apply a similar threshold to the phenotypes, whose selection was based on availability and epidemiologic evidence of their associations with fracture rather than on correlations among them. Because musculoskeletal traits are sexually dimorphic and likely to be influenced by sex-specific genetic mechanisms, (50) the analyses were performed separately in men and women; however, we presented results from the women because the sample size was greater, and women experience more fractures than men. Results in men appear similar; however, our study has insufficient power for a formal comparison of the clustering results between the sexes.…”
Section: Discussionmentioning
confidence: 99%
“…Because musculoskeletal traits are sexually dimorphic and the genetic mechanisms are likely to be sex-specific, (50) the analyses were performed separately in men and women. We focused on results from the 2038 women because osteoporotic fractures are more common in women, genetic regulation has been shown to differ by gender, (50,51) and our sample size for women was greater than for men. …”
Section: Gene Network Inference Via Knowledge-based Data Miningmentioning
confidence: 99%
“…223 Males have larger bones at all ages compared to females, resulting in an increase of whole body strength. Based on remodeling differences, females displayed faster expansion of the femoral neck, leading to potentially increased bone fragility.…”
Section: Bone Structure and Remodelingmentioning
confidence: 99%